Calculation and analysis of IR spectrum of 2-aminopyridine - Akalın, Elif; Büyükmurat, Y.; Özel, Ayşen E.; AKYÜZ, SEVİM (Elsevier, 1999)
Normal coordinate analysis of 2-aminopyridine (2AP) and ND2-pyridine have been performed in valance force field approximation. 2AP was taken as planar because of the low barrier to amino group inversion. The IR absorption intensities have been calculated and the electro–optical parameters (EOP) were fitted to experimental data in order to produce the experimental relative intensities. The created force field and EOP reproduce the IR spectrum of the molecule studied well.
Keywords: Normal coordinate analysis; 2-aminopyridine; IR spectrum; Force field; Electro–optical parameters